2017
DOI: 10.18203/2320-1770.ijrcog20175491
|View full text |Cite
|
Sign up to set email alerts
|

World diabetes day 2017 focus: antepartum hyperglycaemia (or gestational prediabetes) is more in women below 40 years

Abstract: Prediabetes is a state of hyperglycaemia that is above normal, but below blood glucose threshold for diabetes mellitus. As part of the theme for World Diabetes Day of 2017, it has been articulated by the International Diabetes Federation, that up to 16% of births may be affected by this condition and it is estimated that 50% of the affected antenatal patients are under 30 years old. The notion of gestational prediabetes, hyperglycaemia in pregnancy as a clinical condition is yet to be seriously discussed in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The observation that pregnant women with GDM tended to be younger is in line with the observation of Orru MI et al who, speaking of gestational pre-diabetes, had observed that relatively younger pregnant women were also affected and this should not exclude them from screening for GDM [2]. The age level of the pregnant women in this study is comparable to that done by Kodjo Agbeko and by Leye A. who respectively observed mean ages of 30.84 ± 4.17 years [16] and 29.8 ± 6.2 years [9].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The observation that pregnant women with GDM tended to be younger is in line with the observation of Orru MI et al who, speaking of gestational pre-diabetes, had observed that relatively younger pregnant women were also affected and this should not exclude them from screening for GDM [2]. The age level of the pregnant women in this study is comparable to that done by Kodjo Agbeko and by Leye A. who respectively observed mean ages of 30.84 ± 4.17 years [16] and 29.8 ± 6.2 years [9].…”
Section: Discussionsupporting
confidence: 88%
“…Pregnancy follow-up, whatever the level of the health facility, should methodically make it possible to detect glucose intolerance according to the required criteria without missing borderline situations, because of epidemiological presumptions [2], even if it there is some controversy over the standard test for screening [3].…”
Section: Introductionmentioning
confidence: 99%
“…This narrative review was a progression of ongoing studies and started from preliminary evaluations' data that have been previously published [15][16][17][18][19]. There were separate two clinical audits done at secondary and tertiary health facilities in the state [18,19]; plus one expository review [16].…”
Section: Methods Of Evaluation Stakeholdersmentioning
confidence: 99%
“… Lack of follow up of positive cases, which could be due to BCW factors of capacity/knowledge, motivation and opportunity [17].  Several other barriers arising from the health system including limited resources [19] Figure 1: Healthcare workers perception regarding DSME…”
Section: Clinical Medical Reviews and Reportsmentioning
confidence: 99%